Neck circumference is correlated with triglycerides and inversely related with HDL cholesterol beyond BMI and waist circumference. Issue 1 (8th January 2013) - Vallianou, Natalia G.; Evangelopoulos, Angelos A.; Bountziouka, Vassiliki; Vogiatzakis, Evangelos D.; Bonou, Maria S.; Barbetseas, John; Avgerinos, Petros C.; Panagiotakos, Demosthenes B.
Abstract Background Neck circumference, beyond a measure of obesity, is a unique fat depot with increasing significance. This study aimed to investigate the association between neck circumference and biomarkers, indicators of cardiovascular risk. Methods During 2009, 490 volunteers (46 ± 16 years, 40% men) were consecutively enrolled to the study (participation rate 85%). Biochemical analyses were performed through established procedures, and after 12‐h fasting and glucose, total cholesterol, high‐density lipoprotein and low‐density lipoprotein cholesterol, triglycerides, cystatin C, uric acid and high‐sensitivity C‐reactive protein were measured. Anthropometric, lifestyle and dietary characteristics were also recorded to account for potential confounders. Additive linear and logistic regression models were used to evaluate the association between neck circumference and biomarkers of cardiometabolic risk. Results A positive association between neck circumference and systolic and diastolic blood pressure, glucose, triglycerides, uric acid and high‐sensitivity C‐reactive protein, and a negative association with high‐density lipoprotein cholesterol were revealed (all ps < 0.05); models were adjusted for age, gender, years of school, smoking, physical activity status, MedDietScore and alcohol intake. The relationship between neck circumference and high‐density lipoprotein cholesterol, glucose, triglycerides and uric acid remained significant when models were further stratified by body mass index class and abnormal waist circumference. Conclusion Neck circumference was found to be a powerful indicator of atherogenic dyslipidaemia above and beyond central obesity indicators. Copyright © 2012 John Wiley & Sons, Ltd.